Sleep Disturbance and Upper-Extremity Disability - Peters, Rinne Marijn (Arch Bone Jt Surg, 2016)
BACKGROUND: Although upper-extremity disability correlates with psychosocial aspects of illness the association with sleep disturbance in upper extremity disability is less certain. To evaluate whether sleep disturbance is associated with upper-extremity disability among patients with upper extremity illness, accounting for sociodemographic, condition-related, and psychosocial factors. METHODS: A cohort of 111 new or follow-up patients presenting to an urban academic hospital-based hand surgeon completed a sociodemographic survey and measures of sleep disturbance (PROMIS Sleep Disturbance), disability (PROMIS Upper-Extremity Physical Function), ineffective coping strategies (PROMIS Pain Interference), and depression (PROMIS Depression). Bivariate and multivariable linear regression modeling were performed. RESULTS: Sleep disturbance correlated with disability (r=-0.38; P<0.001) in bivariate analysis. Symptoms of depression (r=-0.44; P<0.001) and ineffective coping strategies (r=-0.71; P<0.001) also correlated with upper-extremity specific disability in bivariate analysis. Pain Interference was the only factor associated with disability in multivariable analysis. CONCLUSIONS: Sleep disturbance is not as strongly or directly associated with symptom intensity and magnitude of disability as ineffective coping strategies. Interventions to reduce pain interference (e.g. cognitive behavioral therapy) hold great potential to decrease musculoskeletal symptom intensity and magnitude of disability, and perhaps even sleep disturbance.